Transgenic expression of GFP-LC3 perturbs autophagy in exocrine pancreas and acute pancreatitis responses in mice. Issue 11 (1st November 2020) - Mareninova, Olga A.; Jia, Wenzhuo; Gretler, Sophie R.; Holthaus, Conner L.; Thomas, Diana D. H.; Pimienta, Michael; Dillon, Dustin L.; Gukovskaya, Anna S.; Gukovsky, Ilya; Groblewski, Guy E.
ABSTRACT: Pancreatitis is a common, sometimes fatal, disease of exocrine pancreas, initiated by damaged acinar cells. Recent studies implicate disordered macroautophagy/autophagy in pancreatitis pathogenesis. ATG8/LC3 protein is critical for autophagosome formation and a widely used marker of autophagic vacuoles. Transgenic GFP-LC3 mice are a valuable tool to investigate autophagy ; however, comparison of homeostatic and disease responses between GFP-LC3 and wild-type (WT) mice has not been done. We examined the effects of GFP-LC3 expression on autophagy, acinar cell function, and experimental pancreatitis. Unexpectedly, GFP-LC3 expression markedly increased endogenous LC3-II level in pancreas, caused by downregulation of ATG4B, the protease that deconjugates/delipidates LC3-II. By contrast, GFP-LC3 expression had lesser or no effect on autophagy in liver, lung and spleen. Autophagic flux analysis showed that autophagosome formation in GFP-LC3 acinar cells increased 3-fold but was not fully counterbalanced by increased autophagic degradation. Acinar cell ( ex vivo ) pancreatitis inhibited autophagic flux in WT and essentially blocked it in GFP-LC3 cells. In vivo pancreatitis caused autophagy impairment in WT mice, manifest by upregulation of LC3-II and SQSTM1/p62, increased number and size of autophagic vacuoles, and decreased level of TFEB, all of which were exacerbated in GFP-LC3 mice. GFP-LC3 expression affected key pancreatitis responses; most dramatically, it worsened increases in serum AMY (amylase), a diagnostic marker of acute pancreatitis, in several mouse models. The results emphasize physiological importance of autophagy for acinar cell function, demonstrate organ-specific effects of GFP-LC3 expression, and indicate that application of GFP-LC3 mice in disease models should be done with caution.Abbreviations : AP: acute pancreatitis; Arg-AP: L-arginine-induced acute pancreatitis; ATG: autophagy-related (protein); AVs: autophagic vacuoles; CCK: cholecystokinin-8; CDE: choline-deficient, D, L-ethionine supplemented diet; CER: caerulein (ortholog of CCK); CTSB: cathepsin B; CTSD: cathepsin D; CTSL: cathepsin L; ER: endoplasmic reticulum; LAMP: lysosomal-associated membrane protein; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; TEM: transmission electron microscopy; TFEB: transcription factor EB; ZG: zymogen granule(s).